Strengthen yourself, strengthen your relationships – a self-development based marriage and relationship education program: development and initial pilot-testing - Hardy, Nathan Ray (Kansas State University, 2015)
Marriage and relationship education (MRE) is most commonly delivered in a skills-based format that traditionally centers on teaching couples communication skills. Critiques against the current skills-development approach lead to the development and pilot-testing of an alternative self-development curriculum entitled, “Strengthen Yourself, Strengthen Your Relationships.” Guided by Bowen’s (1978) theory of differentiation, the current study randomly assigned forty couples to the self-development (differentiation) curriculum condition or to a relationship assessment plus feedback condition. Repeated measures ANOVA’s, independent samples t-tests, and regressions were used to analyze the data from pre- to post-test (5 weeks), post-test to follow-up (4 weeks), and pre-test to follow-up (9 weeks). Statistical analyses indicate that women responded more favorably to the feedback condition in terms of differentiation, relationship self-regulation, and problem solving, whereas men responded more favorably to the curriculum condition in terms of relationship self-regulation. Feedback about the curriculum was gathered from participants and was received favorably. Implications from the study suggest that both approaches may have unique value for couples receiving relationship education. Future research should further develop and evaluate the self-development approach in MRE.
Keywords: Relationship Education; Marriage; Communication Skills; Differentiation; Self-Regulation; Couples; Counseling Psychology (0603)